3D printed material application in orthodontics. (2020) - Gupta, Deepak Kumar; Tuli, Ashna; Jain, Ashish
Abstract: The 3D printing has opened new Vistas for dentistry. The 3D printing along with software modelling and thermoforming can help in the design and manufacture of Clear aligners for orthodontic treatment, which is both a contemporary and an esthetic option. Various thermoplastic materials are being currently used worldwide for the manufacture of clear aligners including- polyester, polyurethane, polypropylene, polycarbonates and polyethylene polymers. A pilot investigation of 10 adult patients requiring orthodontic treatment having a mild arch length tooth material discrepancy in either the anterior maxilla or mandible was planned so as to treat patients with aligners. A complete set of orthodontic records including intra and extraoral photographs, lateral cephalogram and OPG, study models were taken. The clear aligners were designed after acquiring an intraoral scan and completing the treatment setup using the virtual software. The virtual stages were developed by Orthoanalyzer software and were 3D printed using two different materials- VeroWhite and VeroClear on a polyjet printer. The clear aligners were manufactured using the standard PET-G material from the stages obtained through 3D printing. The indigenously fabricated clear aligners were found to be an effective orthodontic treatment modality, however there is a learning curve involved in its virtual staging and fabrication. There seems to be a gap between developed virtual stage and actual treatment result obtained.